KEPASTIAN HUKUM MANFAAT PENSIUN MENURUT UNDANG-UNDANG NO. 13 TAHUN 2003 DENGAN UNDANG-UNDANG CIPTA KERJA NO. 11 TAHUN 2020 KLASTER IV DAN PERATURAN PEMERINTAH NO. 45 TAHUN 2015 - Nelson Manalu; Martono Anggusti; Janpatar Simamora (Magister Hukum Universitas HKBP Nommensen, 2021)
Workers at work and when entering retirement age, that in everyday life it is difficult to deny the condition of workers categorized as marginalized (groups), this can be seen through Government Regulation concerning retirement age Number: PER-02/1995 retirement age 55 years and Government Regulation No: 45 of 2015 the retirement age is 56 years and can be extended to 60 years. Whereas in daily reality there are still many workers who work in the formal sector, generally in private companies are employed over the age of 60 years. Whereas according to the labor law, namely Law no. 13 of 2003 article 167 (currently has been removed) the retirement age is not regulated explicitly and only refers to the pension benefit which is regulated by the amount of the pension benefit according to the working period of the worker/laborer. Whereas according to the Job Creation Law, Number 11 of 2020 Cluster IV concerning Employment does not refer to the Government Regulation regulating the retirement age, and the Cluster IV Job Creation Act Number 11 of 2020 only regulates pensions and the nominal value of pension benefits is regulated by Government Regulation Number 35 of 2021.